# math

posted by .

How do you solve 8x^3-24x^2+12x-4=0?

• math -

first step: divide by 4 to make the numbers more manageable:

2x^3 - 6x^2 + 3x - 1 = 0

Now you know that any rational roots will be ±1 or ±1/2

So, try them out. Turns out that none of them is a root.

You can use Descarte's Rule of Signs to show that there are no negative roots, and at most three positive roots (duh).

So, now you have to fall back on the general solution of cubics (very difficult and messy) or iterative methods to get an approximate solution to any desired accuracy.

## Similar Questions

1. ### Algebra (Re.: Reiny)

The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 + b^2)/ab …
2. ### Math

Hello, Having trouble with this one... Solve the inequality: (2x-3)(4x)+x^2=>(3x+4)^2 I did 2x-3*4x 9x^2-12x on the left side on the right side: 9x^2+24x+16 I substracted everything on the right side over to the left and made it …
3. ### pre-calc Question on a previous question

On the question below, Bob Pursley said it was correct, however, I just wanted to make sure that it's not supposed to have another x value since it has x^2 in it. Solve the inequality: (2x-3)(4x)+x^2=>(3x+4)^2 I did 2x-3*4x 9x^2-12x …
4. ### math

24x^4-12x^3+48x^2/-4x=6x^3+3x^2+12x check this for me.
5. ### algebra

24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
6. ### algebra

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
7. ### algebra

Did I do this problem the correct way if so is there a shorter way to explain this?
8. ### Physica

if A=12x - 16y and B= - 24x + 10y,what is the magnitude of the vecror C=2A-B?
9. ### alg2 check?

solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem?
10. ### calculus

i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x^3)^2 i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong. answer: 10x^9 + 36x^8 − …

More Similar Questions